ISLAMIC RELIGIOUS TEACHERS’ EFFORTS TO MOTIVATE STUDENTS AND IMPLEMENT EFFECTIVE ONLINE LEARNING - Idi Warsah (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The Covid-19 phenomenon naturally has an impact on the transformation of learning system from offline to online modes. Thus, this study sought to reveal the efforts made by teachers in Bengkulu province to motivate students during online learning and their efforts to implement effective online learning. 18 teachers who were selected purposively took part as the participants, and they were interviewed to provide information regarding the two objectives of this study. Based on the descriptive qualitative method, the data were analyzed using an interactive analysis model. The findings indicated that in motivating students, the teachers maintained ideal communication, tried to drive students’ emtions to stay involved in learning, made students aware of the essence of the importance of knowledge, simplified learning processes but constructed learning in order to be interesting, provided verbal reinforcement and increased the opportunities of student-teacher interactions, and communicated with parents to help guide their children to study at home. Furthermore, in an effort to implement effective online learning, teachers built disciplined and systematic learning, orientated towards contextual learning contents, and established active interactions with parents and students.